Randomized Control Study of the Implementation and Effects of a New Mental Health Promotion Program to Improve Coping Skills in 9 to 11 Year Old Children: Passport: Skills for Life - Mishara, Brian L.; Dufour, Sarah (Frontiers in Psychology, 2020)
Passport: Skills for Life is a universal, primary school mental health promotion programme to increase children’s coping skills. A stratified randomized control study with pretest, post-test and one-year follow-up included 1,492 3rd to 6th grade children, from higher and lower socio-economic levels, randomly assigned by school to receive the programme or a control group. Implementation, evaluated by questionnaires and focus groups with children, parents and teachers as well as classroom observations, showed that programme activities were well implemented and greatly appreciated, with perceived improvements in resolving conflicts, communicating feelings and coping. Compared to the controls, participants had increased emotional awareness, sustained one year later; conceived of more ways to cope in fictitious situations and reported using more, and more useful strategies, sustained one year later. Positive Academic Behaviours increased, but were not sustained the following year. This is a promising programme to improve coping and emotional awareness that merits further research on its effects.